2015
DOI: 10.1152/ajprenal.00456.2014
|View full text |Cite
|
Sign up to set email alerts
|

Flow regulation of endothelin-1 production in the inner medullary collecting duct

Abstract: Collecting duct-derived endothelin (ET)-1 is an autocrine inhibitor of Na(+) and water reabsorption; its deficiency causes hypertension and water retention. Extracellular fluid volume expansion increases collecting duct ET-1, thereby promoting natriuresis and diuresis; however, how this coupling between volume expansion and collecting duct ET-1 occurs is incompletely understood. One possibility is that volume expansion increases tubular fluid flow. To investigate this, cultured IMCD3 cells were subjected to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
46
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 55 publications
5
46
3
Order By: Relevance
“…This is in line with recent findings demonstrating that blockade of P2Y 2 and P2X 7 receptors inhibits ET-1 production in inner medullary collecting duct cells (22). Furthermore, nonrenal studies demonstrated that purinergic and ET-1 signaling interact in sensory neurons (5), blood vessels (1, 13), as well as myocardium (10).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is in line with recent findings demonstrating that blockade of P2Y 2 and P2X 7 receptors inhibits ET-1 production in inner medullary collecting duct cells (22). Furthermore, nonrenal studies demonstrated that purinergic and ET-1 signaling interact in sensory neurons (5), blood vessels (1, 13), as well as myocardium (10).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that the purinergic receptors might be involved. This idea is originally based on a recent study revealing that P2 receptors are required for flow-stimulated ET-1 release in inner medullary collecting duct cells (22). Our data showed that blockade of medullary P2 receptors by suramin inhibited the diuretic and natriuretic response to increased medullary NaCl loading.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations